ANALYSIS OF RELATIONSHIP AMONG THE FACTORS OF NONEXCUSABLE AFFECTING DELAY IN CONSTRUCTION PROJECT - Satrio Rekso Wilogo; I Putu Artama Wiguna (Journal of Civil Engineering, 2017)
The contribution of the Surabaya construction sector to the growth of the Surabaya economy over the past fewdecades is highly phenomenal, but many of construction projects in Surabaya are experiencing delays. While much researchhas been done about the cause of the delay, but the chronic problem of delay time is still very difficult to clearly discovered.The primary objectives of this research are to identify the main factors of non-excusable delay in construction projects andanalyze the interdependence relationships of one factor with another. Based on literature, structural model has beendeveloped and then use Partial Least Square to analyze the relationships with quantitative impact value among identifiedfactors. In order to collect the data on the measured attributes, a questionnaire survey was designed in the form of anaffirmative question. Respondents for this study are selected from a project manager, head project and director in theSurabaya construction firms were worked on building projects and experienced of dealling delays problem. The results of theresearch suggest that poor field management is one of the most significant factors significant affecting construction projectdelay. While path coefficient of poor capability of contractors and improper planning indicated possitive, neither of these twofactors has any impact on time delay. On the other hand, poor capability of contractor to be one of the key contributingfactors resulting in improper planning and improper planning affecting in poor field management.